2023
DOI: 10.1111/gcb.16654
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and drivers of anaerobic nitrogen transformations in sediments of thermokarst lakes

Abstract: Significant attention has been given to the way in which the soil nitrogen (N) cycle responds to permafrost thaw in recent years, yet little is known about anaerobic N transformations in thermokarst lakes, which account for more than one‐third of thermokarst landforms across permafrost regions. Based on the N isotope dilution and tracing technique, combined with qPCR and high‐throughput sequencing, we presented large‐scale measurements of anaerobic N transformations of sediments across 30 thermokarst lakes ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Denitrification, anammox, and DNRA can occur simultaneously under anaerobic conditions, but their relative contribution to nitrate reduction are highly variable because of their different preferences for substrate availability and other environmental factors (Li et al., 2019; Mao et al., 2023; McTigue et al., 2016). This study first revealed that, at the global scale, the contribution of denitrification to dissimilatory nitrate reduction increased significantly with longitude, while the contribution of DNRA decreased (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…Denitrification, anammox, and DNRA can occur simultaneously under anaerobic conditions, but their relative contribution to nitrate reduction are highly variable because of their different preferences for substrate availability and other environmental factors (Li et al., 2019; Mao et al., 2023; McTigue et al., 2016). This study first revealed that, at the global scale, the contribution of denitrification to dissimilatory nitrate reduction increased significantly with longitude, while the contribution of DNRA decreased (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…The organic C pool in 0–3 m of soils is ~15.3–46.2 Pg (Ding et al, 2016; Wang et al, 2021). Due to the continuous climate warming, the alpine permafrost is rapidly degrading, characterized by the thickening of the active layer (~2 cm year −1 ; Wang et al, 2022) and the widespread occurrence of thermokarst landscape such as thermo‐erosion gully (Yang et al, 2021) and thermokarst lake (Mao et al, 2023; Wei et al, 2021). The permafrost degradation was predicted to result in ~122 Tg (1 Tg = 10 12 g; under Representative Concentration Pathway 4.5, a moderate scenario) and ~300 Tg (under Representative Concentration Pathway 8.5, a worst‐case scenario) of permafrost C release across the plateau by 2099 (Liu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The organic C pool in 0-3 m of soils is ~15.3-46.2 Pg (Ding et al, 2016;Wang et al, 2021). Due to the continuous climate warming, the alpine permafrost is rapidly degrading, characterized by the thickening of the active layer (~2 cm year −1 ; Wang et al, 2022) and the widespread occurrence of thermokarst landscape such as thermo-erosion gully (Yang et al, 2021) and thermokarst lake (Mao et al, 2023;Wei et al, 2021). The permafrost…”
Section: Study Areamentioning
confidence: 99%
“…The dominant permafrost types on the Tibetan Plateau are discontinuous (50%–90%) and sporadic (10%–50%) permafrost (Wang et al, 2022; Zhang et al, 2008), which account for 55.4% and 41.4%, respectively, of the total permafrost area of the region (Figure S1). Over recent decades, the plateau has undergone accelerated soil warming (Ran et al, 2018) and extensive permafrost degradation (Mao et al, 2023; Ni et al, 2021; Xu et al, 2023). Permafrost temperature at a depth of 10 m has increased at an average rate of 0.02–0.78°C decade −1 from 2004 to 2018 (Zhao et al, 2021).…”
Section: Methodsmentioning
confidence: 99%